(untitled) (Global Scientific Review, 2023)
In this article, the role of small business and private entrepreneurship in the service sector in ensuring employment and increasing the income of the population is fully covered, and the criteria, indicators and ways of determining the efficiency of small business and private entrepreneurship in the service sector are developed.